Od umjetnosti riječi do 9. umjetnosti: Vidimo se tamo gore, roman i strip - Iva Šarić ([sic])
Along with the introductory remarks on the relationship between novels and comics and their historically problematic status, this paper analyzes and interprets, from the perspective of creation, i.e. the scriptwriter and the illustrator, as well as from the perspective of the reception or audience, the procedures by which Pierre Lemaitre’s novel Goodbye, Up There is, on the level of content and expression, transformed into the new medium of comics. The comparative narrative analysis of the novel and the comic book shows that the shift from telling to showing mode requires, above all, dramatization, introduction of dialogues, and certain alterations of the plot, focalization, themes, and motivation of characters. These alterations can be linked by the common denominator – adaptation. Adaptation is thus seen as the creative process of transcoding, where the original is reconceived and reinvented in another form of expression, as well as an intertextual process of reception as decoding the narrative.